cAMP During HIV Infection: Friend or Foe? (2012)
ABSTRACT: Intracellular levels of cyclic adenosine 3’,5’-monophosphate (cAMP) are important regulators of immune cells, partially determining the balance between activation and suppression. In this review, we discuss the mecha nisms by which HIV infection increases cAMP levels in T cells, as well as the effect of cAMP on HIV specific responses and its effect on HIV replication and infection. Results suggest that increased cAMP levels during HIV infection may have a dual and opposite roles. On the one hand, they could have a protective effect by limiting viral replication in infected cells and decreasing viral entry. On the other hand, they could have a detrimental role by reducing HIV-specific antiviral immune responses, thus reducing the clearance of the virus and con tributing to T cell dysfunction. Future studies are thus needed to further define the beneficial versus detrimental roles of cAMP, as they could help establish new therapeutic targets to combat HIV replication and/or identify novel ways to boost antiviral immune responses.